PEMBERDAYAAN MASYARAKAT OLEH PEMERINTAH KOTA PEKANBARU MELALUI LEMBAGA PENGEMBANGAN TILAWATIL QUR’AN (LPTQ) KOTA PEKANBARU TAHUN 2019-2022 - Mustakim, Bahri; Hadi, Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The Pekanbaru City Al-Qur'an Tilawatil Development Institute (LPTQ) is an institution operating in the field of Islamic religion which is directly related to the art of reading, writing and deepening the meaning of the contents of the Al-Quran. The problem that occurred in this research is that there are around 4% of the population who are Muslim or as many as 33,284.6 people who still do not have the ability to read the Al-Qur'an and Pekanbaru City's achievement has decreased significantly in Musabaqah Tilawatil Qur'an (MTQ) at the Riau Province level in 2019. The aim of this research was to describe the efforts made by the Pekanbaru City Government in empowering the community through (LPTQ) Pekanbaru City 2019-2022 and to find out the factors that influence community empowerment through (LPTQ) Pekanbaru City 2019-2022. This research uses the theory of community empowerment proposed by Isbandi Rukminto Adi (2013), namely Preparation Stages, Assessment Stages, Planning Stages, Program Implementation Stages and Evaluation Stages. This research uses descriptive qualitative research methods with the main data sources being primary data and secondary data. The data collection techniques used were interview techniques and documentation techniques. This data analysis technique is Data Reduction, Data Presentation, and Drawing Conclusions. The research results show that the Pekanbaru City Government's community empowerment efforts through the Pekanbaru City LPTQ are carried out by means of socialization and work meetings. The inhibiting factor for community empowerment by the Pekanbaru City government through the Pekanbaru City LPTQ is the limited existing budget funds. The supporting factors for community empowerment by the Pekanbaru City government through the Pekanbaru City LPTQ are community participation and support from the government. Keywords: Preparation Stage, Study Stage, Planning Stage, Program and Activity Implementation Stage, Evaluation Stage